OH-65: The earliest evidence for right-handedness in the fossil record. Issue 100 (November 2016) - Frayer, David W.; Clarke, Ronald J.; Fiore, Ivana; Blumenschine, Robert J.; Pérez-Pérez, Alejandro; Martinez, Laura M.; Estebaranz, Ferran; Holloway, Ralph; Bondioli, Luca
Abstract: Labial striations on the anterior teeth have been documented in numerous European pre-Neandertal and Neandertal fossils and serve as evidence for handedness. OH-65, dated at 1.8 mya, shows a concentration of oblique striations on, especially, the left I 1 and right I 1, I 2 and C 1, which signal that it was right-handed. From these patterns we contend that OH-65 was habitually using the right hand, over the left, in manipulating objects during some kind of oral processing. In living humans right-handedness is generally correlated with brain lateralization, although the strength of the association is questioned by some. We propose that as more specimens are found, right-handedness, as seen in living Homo, will most probably be typical of these early hominins.